Health and Caregiving Stress Among Custodial Grandparents in Rural China - Lina Yu; Mohamad Aun, Nur Saadah; Saim, Nor Jana; @Kusenin, Norulhuda Sarnon (Environment and Social Psychology, 2025)
Custodial grandparent families have become common in increased proportion to the old age of the global population. A large percentage of grandparents in rural China have full-time caregiving responsibility due to migration, disease, or death of parents. This qualitative case study examines the health mandates and care-related stresses in custodial grandparents who are working in de-resourced rural settings. The sample was a group of fifteen grandparents (57 to 90 years) who gave primary care to the grandchildren (aged 3 to 16 years). The semi-structured interviews on data collection were then analysed by thematic analysis as supported by the Dual ABCX Model. Three themes were identified that were all intertwined, namely: (1) physical health struggles, (2) emotional distress and grief, and (3) caregiving role strain. Results show that caregiving stress builds up and is guided by various elements that comprise aging, unresolved loss, resource constraint, and high cultural demands of family responsibility. Declines in physical health and emotional burden and care giving demands are not independent problems because over time, they interrelate to limit adaptive capacity in grandparents. The study highlights the necessity of culturally responsive policy and social work intervention, including easy access to healthcare, referring to grief support and respite services, to well serve the rural custodial grandparents.